Niedrigemittierende (Low‐E) Schichten auf KFZ‐Verglasungen. (August 2014) - Gläser, Hans Joachim; Ulrich, Stephan
<x xml:space="preserve">Abstract</x> The influence of low‐emissivity coatings on the outside surface of car glazing Low‐e‐coatings on the outer surface of architectural glazing are used for several years to prevent fog and frost for a clear view in the winter. Also for outdoor parked cars at night they were successfully tested. In the article, the occurrence of condensation on automotive glazing is simulated depending on the weather conditions, the emissivity of the outer surface, day or night, parking or moving vehicle. It is shown that the risk of outside condensation arises from the cooling down of the car cabin below the outside air temperature. The highest risk occurs for inclined windshields at night with clear sky and no wind. With decreasing emissivity, however, it decreases sharply. Further calculations show that due to low‐e‐coatings on the outer surface the solar energy balance Qbal.i of the vehicle cabin increases during daytime. At low solar irradiance this has a positive effect on the cabin climatisation during the heating season, especially in the morning time after outdoor parking. At high irradiation in midsummer, the air conditioner is however only slightly loaded more both when parking as well as driving. With increasing vehicle speed, the heat transfer by the wind compensates more and more the heat radiation to the sky, i. e. the influence of the emissivity on Qbal.i decreases.